Development and Training: The Deployment of Web-based Vaccination Queue system at Military Resort Command 052/Wijayakrama - Jansen Wiratama; Fenina Adilne Twince Tobing; Ririn Ikana Desanti; Suryasari; Wella (I-Com: Indonesian Community Journal, 2023)
Implementing the COVID-19 vaccination queue system by the 052/Wijayakrama Military Resort Command in Tangerang is a form of community service carried out by Multimedia Nusantara University (UMN). This system was created to simplify the vaccination process and reduce the waiting time for vaccination participants. This website-based queuing system is designed with the Laravel framework using the rapid application development model and functionality testing using black box testing. The results of functionality testing of this queuing system indicate that the system can function properly and meet the needs to simplify the vaccination process. More than 1,000 people have used this queuing system, making it easy for the public to get the COVID-19 vaccination. Applying the COVID-19 vaccination queue system by the 052/Wijayakrama Military Resort Command in Tangerang is an example of a technology application to support government programs tackling the COVID-19 pandemic. This system has made it easy for people to get vaccinated and has helped the government to organize and manage the vaccination process better.